PHILOSOPHICAL ANALYSIS OF THE CONCEPT OF NOOSPHERIC DEVELOPMENT IN THE ECOLOGICAL AND GLOBAL SECURITY SYSTEM - Mukhammediyarova , Akhmaral (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
In this article, we will try to reveal the issues of ecological poverty and its philosophical analysis. Because now environmental and global hunger has its relevance in the present time.